Problems and Prospects of Organic Farming in Samastipur District, Bihar, India - Bhushan, Mani; Aditya,; Mandal, Tapan (Indian Journal of Extension Education, 2016)
Bihar is one of the Indian states located in the east where agrarian distress is not a major problem. Crop yields have been  mostly stagnant in the last decades, and coupled with increased input costs, this has led to reduced incomes and debts.  There is an urgent need to study options to improve the sustainability of farming systems in the state which can lead to  better livelihoods of the farmers. One of the strategy to stabilize agriculture in the state is possibly organic farming which  is generally said to have less dependence on external inputs. Organic agriculture is one among the broad spectrum of  production methods that are supportive of the environment. Purposive as well as simple random techniques were adopted  for the study. For selection of district, block, village purposive sampling techniques was employed for selection of  respondent. There are 135 families in the village Srichandpur Kothia which constitute the total population of the study.  Out of 135 families, 100 farmers have been randomly selected for the study. The data using appropriate statistical tools  was analysed taking the support of the package SPSS (Ver. 19). The main issue identified was regarding the problems of  certification. There is no facility for farmers for organic products certification. Due to this problem farmers are not getting  actual price of their produce. Also, the increased demand of food grains for the increasing population in the coming years  would depend more on enhancing productivity through utilization of family labour and farm power per unit of land rather  than expansion of area under cultivation which was mainly observed in the study. It is concluded that organic farming can  be a sustainable farming practice in Bihar depending on regional conditions and the crops cultivated. Policies stimulating  organic farming and certification should therefore consider the farmer's preferences for sustainable livelihoods.
Keywords: Bihar; Organic farming; Problem; Policy; Certification